Factores tributarios que desalientan la formalización de los comerciantes de confecciones de la calle 9 de diciembre del mercado de Belén, Iquitos – 2021 - Babilonia Medina Jeymi Esmeralda (2023)
The present study entitled "Tax Factors that discourage the Formalization of Garment Merchants on Calle 9 de Diciembre in the Belén Market, Iquitos 2021" was carried out with the objective of determining which are the factors that discourage the formalization of garment merchants. For this, the descriptive type of research was used and the research design was Non-Experimental, 18 merchants who have their respective space and table were taken into account as the study population, to whom a survey was applied with the instrument data collection called questionnaire; Concluding that the lack of tax knowledge, the lack of understanding of tax laws and regulations, and tax evasion are the tax factors that discourage the formalization of clothing merchants on December 9th Street in the Belén Market, Iquitos- 2021, added to them is also the perception of the more use that the government makes of the taxes collected.